An Epstein-Barr virus-specific cytotoxic T cell epitope in EBV nuclear antigen 3 (EBNA 3) (The Rockefeller University Press, 1990)
Epstein-Barr virus (EBV)-specific CTL clones were isolated that recognized A-type EBV transformants but not B-type transformants. These A-type-specific CTL clones (HLA B8 restricted) were used to screen peptides derived from the EBV nuclear antigens (EBNAs) 2, 3, 4, and 6 as potential CTL epitopes. Of the 76 peptides screened, one sequence from EBNA 3 (residues 329-353) was recognized by A-type-specific CTL clones after absorption onto target cells (either autologous B-type transformants or PHA blasts). This report is the first description of an EBV target epitope recognized by specific CTL clones.